Brain Atrophy and Clinical Characterization of Adults With Mild Cognitive Impairment and Different Cerebrospinal Fluid Biomarker Profiles According to the AT(N) Research Framework of Alzheimer’s Disease - Rivas-Fernández, Miguel Ángel; Lindín, Mónica; Zurrón, Montserrat; Díaz, Fernando; Aldrey-Vázquez, José Manuel; Pías-Peleteiro, Juan Manuel; Vázquez-Vázquez, Laura; Pereiro, Arturo Xosé; Lojo-Seoane, Cristina; Nieto-Vieites, Ana; Galdo-Álvarez, Santiago (Frontiers in Human Neuroscience, 2022)
Introduction: The present study aimed to evaluate, in adults with mild cognitive impairment (MCI), the brain atrophy that may distinguish between three AT(N) biomarker-based profiles and contrasting its clinical value. Methods: Structural MRI was employed to evaluate volume and cortical thickness differences in MCI patients with different ATN profiles: A-T-N-: Normal AD biomarkers; A+T-N-: AD Pathologic Change; and A+T+N+: Prodromal AD. Sensitivity and specificity of these changes were estimated. Results: An initial atrophy in MTL areas was found in the A+T-N- and A+T+N+ groups, spreading towards parietal and frontal regions in A+T+N+ patients. These structural changes allowed distinguishing ATN profiles within the AD continuum; however, the profiles and their pattern of neurodegeneration were unsuccessful to determine the current clinical status. Conclusions: Structural MRI is useful to determine the specific brain structural changes of AT(N) profiles along the AD continuum, allowing differentiation between MCI adults with or without pathological AD biomarkers.